2010
DOI: 10.1002/art.27318
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of interleukin‐7 in labial salivary glands of patients with primary Sjögren's syndrome correlates with increased inflammation

Abstract: Objective. To study the expression levels and immunostimulatory capacities of interleukin-7 (IL-7) in primary Sjögren's syndrome.Methods. Labial salivary gland (LSG) IL-7 expression was determined by immunohistochemistry, using a quantitative scoring system, in 30 patients with sicca syndrome: 15 patients with primary Sjögren's syndrome (SS) and 15 patients with non-SS sicca syndrome. The correlation of IL-7 expression in LSGs with parameters of local and peripheral disease was studied, and serum and salivary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 33 publications
7
71
0
Order By: Relevance
“…However, we hypothesize that when increased IL-7 is prolonged, compromised Treg function increases the risk of expanding autoreactive T cells, or in the case of graft-versus-host disease and transplantation, alloreactive T cells. Consistent with this, IL-7 concentration is increased in the synovial fluid of patients with rheumatoid arthritis (39), the cerebrospinal fluid of patients with multiple sclerosis (10), and the salivary glands of patients with Sjögren's syndrome (40). Moreover, the major sources of IL-7 are stromal cell populations hosted in bone marrow niches (41) that house Tregs (42) and that support extensive proliferation of bone marrow resident mature T cells, including diabetogenic (43) and colitogenic (44) T cells.…”
Section: Discussionmentioning
confidence: 66%
“…However, we hypothesize that when increased IL-7 is prolonged, compromised Treg function increases the risk of expanding autoreactive T cells, or in the case of graft-versus-host disease and transplantation, alloreactive T cells. Consistent with this, IL-7 concentration is increased in the synovial fluid of patients with rheumatoid arthritis (39), the cerebrospinal fluid of patients with multiple sclerosis (10), and the salivary glands of patients with Sjögren's syndrome (40). Moreover, the major sources of IL-7 are stromal cell populations hosted in bone marrow niches (41) that house Tregs (42) and that support extensive proliferation of bone marrow resident mature T cells, including diabetogenic (43) and colitogenic (44) T cells.…”
Section: Discussionmentioning
confidence: 66%
“…In a mouse model for rheumatoid arthritis, anti-IL-7 treatment completely inhibited autoimmune arthritis (51). Moreover, IL-7 expression is increased in the inflamed salivary glands in primary Sjögren's syndrome compared with non-Sjögren's sicca syndrome patients (52).…”
Section: Discussionmentioning
confidence: 97%
“…Considering that autoimmune diseases are thought to be promoted by IL-7, these are unexpected results. Indeed, some authors have shown that IL-7 signaling could be involved in the pathogenesis of types 1 diabetes [22,23], Sjögren syndrome [24] or systemic lupus erythematosus [25] and IL-7Ra blockade could prevent or reverse these diseases. Nevertheless, our present results are confirmed by those of previous clinical studies assessing the expression of IL-7 in other autoimmune conditions.…”
Section: Gd-total (N = 37) Gd-active (N = 15) Gd-inactive (N = 8) Gd-mentioning
confidence: 99%